2021
DOI: 10.1136/bjsports-2020-103596
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of treatments for acute and subacute mechanical non-specific low back pain: a systematic review with network meta-analysis

Abstract: ObjectiveTo assess the effectiveness of interventions for acute and subacute non-specific low back pain (NS-LBP) based on pain and disability outcomes.DesignA systematic review of the literature with network meta-analysis.Data sourcesMedline, Embase and CENTRAL databases were searched from inception until 17 October 2020.Eligibility criteria for selecting studiesRandomised clinical trials (RCTs) involving adults with NS-LBP who experienced pain for less than 6 weeks (acute) or between 6 and 12 weeks (subacute)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 56 publications
(69 reference statements)
4
65
0
3
Order By: Relevance
“…Ruddock et al found similar results (SMD of −0.36) in support of the efficacy of SMT for LBP intensity in the short term ( 108 ). Along the same lines, a recent network meta-analysis found that manual therapy (including SMT) significantly reduced pain and disability in the short and intermediate terms compared with inert treatment for acute and subacute LBP ( 109 ). Specifically, manual therapy was reported to be the most effective non-pharmacologic approach.…”
Section: Efficacy Of Spinal Manipulative Therapy For Low Back and Nec...mentioning
confidence: 90%
“…Ruddock et al found similar results (SMD of −0.36) in support of the efficacy of SMT for LBP intensity in the short term ( 108 ). Along the same lines, a recent network meta-analysis found that manual therapy (including SMT) significantly reduced pain and disability in the short and intermediate terms compared with inert treatment for acute and subacute LBP ( 109 ). Specifically, manual therapy was reported to be the most effective non-pharmacologic approach.…”
Section: Efficacy Of Spinal Manipulative Therapy For Low Back and Nec...mentioning
confidence: 90%
“…Example: ‘Data availability statement. Data are available in a public, open access repository: https://osf.io/q24xh’ 77 [the authors provide the dataset of included studies (with reasons for excluding studies from meta-analysis), and a list of excluded studies with reasons].…”
Section: Implementing the Prisma 2020 Statement: Examples For Sport A...mentioning
confidence: 99%
“…Esempio: «Dichiarazione sulla disponibilità dei dati. I dati sono disponibili in un archivio pubblico ad accesso aperto: https://osf.io/q24xh' 77 [gli autori forniscono il set di dati degli studi inclusi (con i motivi per l'esclusione degli studi dalla meta-analisi) e un elenco di studi esclusi con le motivazioni].…”
Section: Altre Informazioni Item 26: Conflitti DI Interesseunclassified